Pengaruh Ukuran Perusahaan, Profitabilitas terhadap Nilai Perusahaan dengan Struktur Modal Sebagai Variabel Intervening pada Perusahaan Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia (BEI) - Cindy Astuti; Sri Hermuningsih; Ratih Kusumawardhani (J-MAS (Jurnal Manajemen dan Sains), 2023)
The purpose of this study was to determine the effect of company size, profitability on firm value with capital structure as an intervening variable in food and beverage companies listed on the IDX for the 2017-2021 period. This study uses a type of quantitative research with sampling using a purposive sampling method, which is a sample selection method with certain predetermined criteria. So that in this study obtained as many as 25 data from 72 companies that meet the criteria. The method used in this study is linear regression analysis with SPSS version 20. The results of this study found that (1) company size has a positive effect on capital structure (2) profitability has a significant negative effect on capital structure (3) company size has a positive and no effect significant to firm value (4) profitability has a significant positive effect on firm value (5) capital structure is able to mediate the effect of firm size on firm value (6) capital structure is unable to mediate the effect of profitability on firm value.